Benefits of organic agriculture for environment and animal welfare in temperate climates - Jürn Sanders; Jan Brinkmann; Lucie Chmelikova; Florian Ebertseder; Annette Freibauer; Frank Gottwald; Almut Haub; Michael Hauschild; Johanna Hoppe; Kurt-Jürgen Hülsbergen; Rüdiger Jung; Daniel Kusche; et al. (Organic Agriculture, 2025)
Although scientists have been researching the impacts of organic agriculture on the environment and animal welfare for decades, the conclusions drawn by the scientific community remain controversial. Against this background, this paper provides a comprehensive assessment of the benefits of organic farming in both areas by analysing results of all relevant scientific comparative studies between organic and conventional farming that have dealt with this topic over the last thirty years. So far, this study is the largest one of its kind and the first one that adds the aspect of animal welfare to a comprehensive array of impact categories. The systematic review of the scientific literature from pairwise comparisons found that organic management showed clear advantages over conventional management in the fields of environmental protection and resource conservation, which can be mainly explained by the system approach pursued in organic farming. No clear conclusion was drawn regarding animal welfare indicating that farm-specific management factors are of greater importance than the production system (organic vs conventional). Consequently, organic farming may contribute to solving current environmental and resource challenges and is rightly considered a key approach for sustainable land use. The positive effects should be further strengthened by decreasing the yield gaps between organic and conventional farming, i.e. by improving yields based on organic principles as well as by altering their relevance through changes in consumption as feed for livestock and food for humans.

Farmers taking responsibility for herd health development—stable schools in research and advisory activities as a tool for dairy health and welfare planning in Europe - Silvia Ivemeyer; Nick J. Bell; Jan Brinkmann; Kornel Cimer; Elisabeth Gratzer; Christine Leeb; Solveig March; Cecilie Mejdell; Stephen Roderick; Gidi Smolders; Michael Walkenhorst; Christoph Winckler; et al. (Organic Agriculture, 2015)

Improvement of animal health in organic dairy farms through ‘stable schools’: selected results of a pilot study in Germany - Solveig March; Jan Brinkmann; Christoph Winckler (Organic Agriculture, 2014)